Strategi Perilaku Sosial dalam Masyarakat Indonesia Kontemporer: Perspektif pendidikan, ekonomi, dan interaksi sosial mahasiswa - Kuswandana, Belva Lauda (Maliki Interdisciplinary Journal, 2026)
This study examines the dynamics of social behavior in contemporary Indonesian society from the perspectives of social education, impulsive buying behavior among students, prosocial behavior, and the social behavior formation of young adults. Amid rapid socio-cultural transformation and increased technology use, Indonesian society faces new challenges, particularly in social interaction, economic decision-making, and responding to changes in the social environment. This research synthesizes four scholarly articles published in the repository and scientific journals of UIN Maulana Malik Ibrahim Malang. First, the study on prosocial behavior elucidates how individuals’ tendencies toward actions benefiting others form the foundation of social interaction in national and societal life (Islamy, 2015). Second, research on economic literacy and self-control among students describes the relationship between economic literacy, self-control, and impulsive purchasing behavior of millennials—a phenomenon highly relevant in the current digital era (Atunnisa’ & Firdiansyah, 2022). Third, the article on social cultural behavior, politics, and religious activities in Indonesian society highlights how cognitive, affective, and evaluative orientations shape political culture and religious relations in a pluralistic society (Zuhroh, 2014). Fourth, the LoroNG journal study on the impact of parenting patterns on Generation Z’s social behavior offers significant insights into the role of family education in shaping social character among Indonesian youth (Reynata & Zahro, 2024). The synthesised findings show that social behavior in Indonesia is influenced by educational structures, family dynamics, economic conditions, and patterns of social interaction. This study emphasizes the importance of interdisciplinary social science approaches to enhance understanding of human behavior within the dynamic socio-cultural landscape.